Improvement of exercise and functional capacity and quality of life in patients with heart failure by iron therapy - Deichl, Andrea; Edelmann, Frank (Frontiers in Cardiovascular Medicine, 2023)
Heart failure (HF) is one of the most common causes of death in industrialized countries and increases steadily with age. Patients with HF present many comorbidities that affect their clinical management, quality of life, and prognosis. Iron deficiency is a relevant comorbidity of all patients with heart failure. It remains the most prevalent nutritional deficiency worldwide, affecting an estimated 2 billion people and has a negative prognostic impact on hospitalization and mortality rate. To date, none of the previous studies, have provided evidence of reduced mortality or decrease in hospitalization with intravenous iron supplementation. This review describes the prevalence, clinical implications, and current trials on the treatment of iron deficiency in heart failure and discusses the Improvement of exercise and functional capacity and quality of life in patients with heart failure by iron therapy. Despite compelling evidence of the significant prevalence of ID in HF patients and current guidelines, ID is often not properly managed in clinical practice. Therefore, ID should be given greater consideration in HF health care practice to improve patient quality of life and outcome.